Individual migration strategy fidelity but no habitat specialization in two congeneric seabirds. (30th October 2020) - Merkel, Benjamin; Descamps, Sébastien; Yoccoz, Nigel G.; Grémillet, David; Daunt, Francis; Erikstad, Kjell E.; Ezhov, Aleksey V.; Harris, Mike P.; Gavrilo, Maria; Lorentsen, Svein‐Håkon; Reiertsen, Tone K.; Steen, Harald; et al.
Abstract: Aim: In migratory species, individuals often use fixed and individual‐specific migration strategies, which we term individual migration strategy fidelity (IMSF). Our goal was to test if guillemots have flexible or fixed individual migration strategies (i.e. IMSF), if this behaviour is consistent across large parts of the genus' range and if they were philopatric to geographical sites or a habitat feature. Location: North Atlantic. Taxon: Uria spp. Methods: We quantified consistent individual differences in inter‐annual spatial distribution and habitat occupied throughout the non‐breeding period using a large geolocator tracking dataset of 729 adult seabirds breeding at 13 colonies across the Northeast Atlantic and repeatedly tracked up to 7 years over a 9‐year period. Additionally, we used a similarity index to calculate relative fidelity to either geographical sites or habitats and linear mixed‐effects models to assess persistence of spatial site fidelity over multiple years. Results: Both guillemot species exhibited IMSF across a large part of the genus' range which persisted over multiple years. Individuals of both species and almost all colonies showed fidelity to geographical sites and not to specific habitats. Main conclusions: Guillemots show IMSF that is best explained by site familiarity (fidelity to specific sites) rather than habitat specialization (fidelity to specific habitats). In the context of rapidly changing environments, favourable habitats may permanently shift locations and hence species displaying IMSF driven by site familiarity—such as the genus Uria —may not be able to adjust their migration strategies sufficiently fast to sustain individual fitness and ensure population persistence.